Disrupting Savagism : Intersecting Chicana/o, Mexican Immigrant, and Native American Struggles for Self-Representation - Aldama, Arturo J., 1964- (Book collections on Project MUSE., 2001)
Comparative study through discourses by Gaimo, Silko, Anzaldua and others examining the disruption of the boundaries of class, gender, race, ethnicity, and sexuality in Chicano, Mexican and Native American immigrants in the Americas.